Prazer e sofrimento: faces das vivências subjetivas do trabalho de estagiários de uma instituição pública do Poder Judiciário - Lima, Larissa Simões de (Brasil, 2023)
This research aimed to investigate the experiences of pleasure and suffering related to the universe of work of administration trainees, who carry out their activities in an administrative sector of a public institution of the Judiciary System of the State of Amazonas. The research is based on the theoretical contributions proposed by Psychodynamics of Work, which allows the researcher to consider the subjective aspects that are present within the work environment, in order to understand their relations and beneficial or harmful influences on the intern's experience. Therefore, the collection of these data was achieved through interviews with a semi-structured script, so that their reading and interpretation were analyzed according to the methodology adapted from the Clinical Analysis of Work. The results obtained reveal a fragment of how the organization of work contributes to triggering suffering for the interns, due to the fact that it is characterized by hierarchical relationships, by a restricted and solitary work model, by the lack of institutional actions aimed at bringing the collective of interns and the lack of appreciation. On the other hand, it was also evidenced that the interns mobilize subjectively to subvert suffering into pleasure, given the strategies used in the face of the difficulties encountered in carrying out the work, in circumventing the prescriptions to adapt to the reality of the work. Recognition by hierarchical superiors, gains at symbolic levels, represented by the development of skills, acquisition of knowledge and experience, and gains at material levels, represented by the internship grant, are shown to be sources of achievements and experiences of pleasure, which allow interns to remain engaged in carrying out their work.